Melanoma ganglionic metastasis 30 years after treatment of the primary tumor: a case report - Tincani, Alfio José (1996)
The recurrence of melanoma in patients is well-documented, and is dependent on a number of factors. We report a case in which a patient had a case of ganglionar metastasis in the neck after a 30-year disease-free interval following primary treatment.